The results of the experiments on the culture of flounder Platichtyhys flesus luscus (Pallas, 1811) and turbot Psetta maeotica (Pallas, 1811) at the Romanian Black Sea coast - Zaharia T.; Alexandrov L.; Zaharia M.; Bilal I. (Recent advances in Mediterranean aquaculture finfish species diversification, 2000)
The paper includes the experiments carried out in 1994-1997 at RMRI Constanta concerning the culture of flounder and turbot, using populating material obtained through controlled spawning. Reproduction was made with wild animals bred in captivity, which released good quality seminal products by about six months from their catch for flounder and about nine months for turbot, without hormonal stimulation. Fecundation percentages varied between 10 and 80 per cent for flounder and between 20 and 70 per cent for turbot, and those of hatching between 20 and 50 per cent for flounder and between 10 and 90 per cent for turbot. The culture of turbot juveniles started from wild specimens weighing 2-4 g each (3-4 months old), and their mean weights were 100 g each at the age of 1.5 years, 350 g each at 2.5 years and 750 g each at 3.5 years old, without providing them the best culture conditions.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Recent advances in Mediterranean aquaculture finfish species diversification', 1999/05/24-28, Zaragoza (Spain)